Continuidade de políticas públicas: a constitucionalização importa? - Lima, Giovanna de Moura Rocha (2011)
The purpose of this dissertation is to understand in which ways the constitution affects the continuity of public policies that have been constitutionalized. Deriving from the literatures on constitutionalism and public policy I suggest an analysis model in which the explanation of the continuity of constitutionalized policies – my dependent variable – is the result of its constitutional status and sources of resilience – my independent variables. My focus at this point in time is theoretical but it is empirically oriented, so I roughly suggest paths that would lead to the verification of the hypothesis and suggestions I make here.